Urgensi Moratarium Terhadap Perjanjian Peningkatan dan Perlindungan Penanaman Modal (P4M) Terkhusus pada Mekanisme Penyelesaian Sengketa yang Merujuk pada International Centre For The Settlement Of Investment Dispute (ICSID) - Fahlevy, Syahrizal (UNES Law Review, 2023)
This study discusses agreements regarding various issues that arise in connection with the Enhancement and Protection of Foreign Investment (P4M) as agreements that encourage protection against capital restrictions, but often cause lawsuits that can cause losses from the Indonesian side. Therefore, it is necessary to have a P4M moratorium so that Indonesia needs to review clauses that are detrimental to Indonesia and carry out renegotiations with foreign parties. In the event that a dispute arises between Indonesia and foreign investors, it can be resolved through The International Center for the Settlement of Investment Dispute (ICSID) by taking into account the interests of Indonesia. This research was conducted in a juridical-normative way with a literature study.